Characterization of transcriptional complexity during pre‐implantation development of the yak (Bos grunniens) using RNA‐Seq. (26th March 2018) - Zi, X‐D; Luo, B; Xia, W; Zheng, Y‐C; Xiong, X‐R; Li, J; Zhong, J‐C; Zhu, J‐J; Zhang, Z‐F
Contents: The objective of this study was to investigate the mechanism that regulates pre‐implantation development of the yak ( Bos grunniens ). We determined the transcriptomes of in vitro ‐ produced yak embryos at two‐cell, four‐cell, eight‐cell stages, and morula and blastocyst using the Illumina RNA‐seq for the first time. We obtained 47.36–50.86 million clean reads for each stage, of which, 85.65%–90.02% reads were covered in the reference genome. A total of 17, 368 genes were expressed during the two‐cell stage to blastocyst of the yak, of which 7, 236 genes were co‐expressed at all stages, whereas 10, 132 genes were stage‐specific expression. Transcripts from 9, 827 to 14, 893 different genes were detected in various developmental stages. When |log2 ratio| ≥ 1 and q ‐value <0.05 were set as thresholds for identifying differentially expressed genes (DEGs), we detected a total of 6, 922–10, 555 DEGs between any two consecutive stages. The GO distributions of these DEGs were classified into three categories: biological processes (23 terms), cellular components (22 terms) and molecular functions (22 terms). Pathway analysis revealed 310 pathways of the DEGs that were operative in early pre‐implantation yak development, of which 32 were the significantly enriched pathways. In conclusion, this is the first report to investigate the mechanism that regulates yak embryonic development using high‐throughput sequencing, which provides a comprehensive framework of transcriptome landscapes of yak pre‐implantation embryos.